QUANTITATIVE TECHNIQUES IN BUSINESS - Gaurav verma (International Journal of Research Science and Management, 2016)
A systematic approach to decision making is complex because today's business and environment in which it is functioning are for more complex than in the past. For large business a single wrong decision very painful but may also have ramifications in national economy. The objective of this paper is to discuss the various quantitative techniques and methods used in managerial decisions. Quantitative techniques are very powerful medium through which we solve uncertainty in decision making and enhance projectability and efficiency in the business. Therefore, these quantitative techniques evaluate planning factors and when these arise then provide meaningful solution to particular business problem.